Microemulsions, Micelles, and Functional Gels: How Colloids and Soft Matter Preserve Works of Art. Issue 25 (26th March 2018) - Chelazzi, David; Giorgi, Rodorico; Baglioni, Piero
Abstract: Colloid science provides fundamental knowledge to fields such as the pharmaceutical, detergency, paint, and food industry. An exciting application is art conservation, which poses a challenge owing to the complex range of interfacial interactions involved in restoring artefacts. Currently, the majority of the most performing and environmentally safe cleaning and consolidation agents for artworks belong to soft matter and colloids. The development and application of increasingly complex systems, from microemulsions to semi‐interpenetrating hydrogels containing such fluids, is presented. These systems have been used on diverse artefacts, from Renaissance frescos to works by Picasso and Pollock. Chemical design can be implemented to meet the requirements of curators, and knowledge of the colloid structure and dynamics can overcome serendipitous approaches of traditional conservation practice. Future perspectives for soft matter and colloid science in the field of cultural heritage preservation are also summarized. Abstract : Colloids and soft matter provide systems that enable the selective removal of soil and aged coatings from works of art. Microemulsions and micelles favour the de‐wetting and detachment of polymer films from artistic surfaces; the detached films can be easily removed, recovering the artefact's aesthetic appearance. Gels can confine the cleaning fluids and release them gradually, avoiding overcleaning and leaching of original components.